From sabotage to support : a new vision for feminist solidarity in the workplace - Wiggins, Joy L.; Anderson, Kami, 1975- (Berrett-Koehler Publishers, 2019)
This book examines how the dynamics of privilege and power have played out in the history of the feminist movement and identifies socialized behaviors and ideologies that trigger implicit bias and microaggressions. Tools are provided to interrupt negative thoughts and actions so women can nurture mutual support and show up as their authentic selves.